Electrical Cardiometry Versus Carotid Doppler in Assessment of Fluid Responsiveness in Critically Ill Septic Patients. Issue 4 (2nd December 2021) - Effat, Hassan; Hamed, Khaled; Hamed, Gamal; Mostafa, Rania; El Hadidy, Samir
Abstract: Background: It is now widely recognized that both inadequate and excessive fluid replacement are deleterious to health, and both can affect recovery during critical illness. Objective: We had investigated the accuracy of electrical cardiometry (EC) and carotid artery flow measurement in assessment of fluid responsiveness in critically ill septic patients and also had evaluated the accuracy of passive leg raising (PLR) maneuver in evaluation of fluid responsiveness. Methods: Fifty critically ill septic patients were enrolled in this study. Results: Our study results showed that 45.5% ( n  = 20) of the study population were fluid responder. PLR test could assess fluid responsiveness with specificity 100% and sensitivity 95% with cut off 11.6% changes in COP to predict fluid responsiveness. We found a statistically significant moderate positive correlation between common carotid artery (CCA) blood flow (BF CCA) both after PLR and fluid challenge (FC) and an agreement analyses between carotid blood flow measurement and Doppler echocardiography measurement with kappa value 0.906 and 0.954 after PLR and FC, respectively, and P value <.001. We also found that an overall good agreement between EC measurement % of change cardiac output (%COPEC ) and % of change cardiac output (COP) by echocardiography with kappa value >0.6 and P value <.001 so we can use this parameters to predict fluid responsiveness post PLR and FC. Conclusion: Electrical cardiometry and carotid Doppler can be used to predict fluid responsiveness often both PLR and FC in critically ill septic patients.